Nanozyme based ultra-stretchable, low-hysteresis, and dual-mode antibacterial composite hydrogels for wound healing - Yanyan Li; Weiqi Kang; Jian Zhang; Ping Shi; Jianshu Li; Yongping Lu (Materials Today Bio)
Wound care always presents challenges as they are susceptible to bacterial infections and have mechanical compatibility issues with wound dressings, leading to a delayed recovery of the structure and functional integrity of skin tissue. Herein, an iron-based metal-organic framework loaded with gold (Fe-MIL-88NH2-Au) nanozyme based composite hydrogel (HMAux) with excellent mechanical compatibility and dual-mode antibacterial properties was designed for wound care. To obtain HMAux, Fe-MIL-88NH2-Au nanozyme with photothermal properties and peroxidase-like and oxidase-like activities was prepared. Then it was introduced into the hydrogel system with a sea-island structure which was prepared via the copolymerization of acrylamide and acryloyl Pluronic F127 (PF127-DA) in the aqueous solution. Using dynamic micelles as the energy dissipation mechanism, double bonds and intermolecular interactions as two crosslinking methods in HMAux make it possess good stretchability (3244 %–4524 %), toughness (593.8 kJ/m3 to 421.5 kJ/m3), and low hysteresis (0.13–0.15). Furthermore, the synergistic photothermal and chemodynamic effects provide good antibacterial performance under mild conditions, with killing rates of approximately 95.02 % and 97.28 % for S. aureus and E. coli, respectively. In vivo experiments have proved that HMAux can effectively adapt to the contour of the wound and treat wound infections.